(11x+22)(2x-18)=

Simple and best practice solution for (11x+22)(2x-18)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11x+22)(2x-18)= equation:


Simplifying
(11x + 22)(2x + -18) = 0

Reorder the terms:
(22 + 11x)(2x + -18) = 0

Reorder the terms:
(22 + 11x)(-18 + 2x) = 0

Multiply (22 + 11x) * (-18 + 2x)
(22(-18 + 2x) + 11x * (-18 + 2x)) = 0
((-18 * 22 + 2x * 22) + 11x * (-18 + 2x)) = 0
((-396 + 44x) + 11x * (-18 + 2x)) = 0
(-396 + 44x + (-18 * 11x + 2x * 11x)) = 0
(-396 + 44x + (-198x + 22x2)) = 0

Combine like terms: 44x + -198x = -154x
(-396 + -154x + 22x2) = 0

Solving
-396 + -154x + 22x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '22'.
22(-18 + -7x + x2) = 0

Factor a trinomial.
22((-2 + -1x)(9 + -1x)) = 0

Ignore the factor 22.

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Solution

x = {-2, 9}

See similar equations:

| -5x-9=3x+y | | k-8k=0 | | -5+-x= | | 100=5x-2y+85 | | 9x+30=4x+105 | | y=(x-5i)(x+5i) | | 18x=-100-2x | | 75/c=15/8 | | 10z+9=2 | | 3x-3/x-1=2x/x | | (x*2)+(y*4)=99 | | 7.15x+16=51.1225+4x | | y=0.15x+49 | | 35=(f-32)5/9) | | 8z+2=10 | | -2-x=15 | | log(19)=0.471 | | 14.5x=19.5y | | x=6/x-1 | | x-y=117 | | W+1.6=13 | | log(19)4=0 | | (3x^3+3x^2+4x+7)+(5x^3+2x^2+x+9)= | | 7.5h=3.2 | | 7.8a+15=100.8 | | sqrt(4x+9)-8=5 | | 1/5d=72 | | 3x+2=-x-6 | | 14=n/5 | | -2w=15 | | -13m=-14-6m | | -13m=-14-6 |

Equations solver categories